Interactive Video-Based Experiential Learning Model and its Effect on Islamic Religious Education Learning Outcomes - Rodiani Puspita Sari; Erlina Erlina; Sunarto Sunarto (STAI Serdang Lubuk Pakam, 2025)
Islamic Religious Education learning in junior high schools still faces serious challenges, particularly low student engagement and limited use of learning media that encourages higher-order thinking. This condition has an impact on low evaluative cognitive achievement (C5), which requires the ability to assess, make decisions, and provide rational justifications. At Muhammadiyah 3 Junior High School in Bandar Lampung, the Islamic Religious Education learning process is still dominated by lecture methods with minimal use of interactive media. This study aims to analyze the effect of the Experiential Learning model based on interactive videos on Islamic Religious Education learning outcomes at the C5 cognitive level. The study uses a quantitative approach with a quasi-experimental method and a post-test only control group design. The sample consisted of two classes, namely class VIII-A as the control group and VIII-B as the experimental group. The results of the t-test analysis showed a significance value of 0.000 (p < 0.05), which indicates a significant effect on student learning outcomes. These findings indicate that the interactive video-based Experiential Learning model is effective in improving students' evaluative abilities. Implicitly, this model can be used as a strategic alternative to develop contextual and meaningful Islamic Religious Education learning.